IDENTIFIKASI JENIS HAMA DAN PENYAKIT TANAMAN MERANTI MERAH (Shorea leprosula Miq) DI AREAL KEBUN BENIH SEMAI UNIVERSITAS PALANGKA RAYA: Identification of Pest and Disease of Red Meranti (Shorea leprosula Mig) in the Seed Garden, Palangka Raya University - Cimi Trilia; Eritha K. Firdara; Reri Yulianti (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
Seed gardens are one way to obtain quality seeds. Seed gardens are areas where certainplants are planted to produce seeds of superior genetic origin. The seed garden of TheUniversity of Palangkaraya in maintaining red meranti (Shorea leprosula Miq) plantsencountered several obstacles, one of which was pests and diseases. Identification of pestand disease attacks is basically the beginning to find out a plant needs special care orattention to improve the quality of the plant itself. This study aims to identify anddetermine the intensity of pest and disease attacks on red meranti (Shorea leprosula Miq)in the seed garden area of The University of Palangka Raya. Collecting data using thecircle plot method, a systematic random sampling technique. Based on the research, it wasfound that the types of pests and diseases that attack red meranti are fire caterpillar(Setothosea asigna), beetle (Mecynorrhina sp), leaf spot (Curvularia sp and Nigrosporasp). The frequency of pest attack is 7.52% and the intensity of attack is 0.75%, with acombination frequency of 1.50% and an attack intensity of 0.45%.Keywords: identification, pests, diseases, seed garden